Encaustic art - Margell, Jennifer (Parkstone International, 2013)
Encaustic painting is one of the world's most venerable art forms, having been practised consistently around the world since the ancient Egyptians first used it to decorate sarcophagi, and enjoying continuing popularity in the modern era with artists such as Paul Klee and Diego Rivera. In this new text, Jennifer Margell offers readers a comprehensive introduction to the medium, featuring instructive how-tos for encaustic art beginners, revealing interviews with some of the most celebrated practitioners of the medium, and a gallery featuring one of the largest published collections of encaustic art to date.